Evaluation of Clean Water Distribution Development in Bee Timor-Leste, E.P Post Administrative Dom Aleixo Dili Municipality - Sri Sumiyati; Zeferino Soares Lopes; M Arief Budihardjo (Neutron, 2022)
Post Administrative Dom Aleixo is a part of Dili City which acts as the central government with an area of 33.12 km2, total population in 2015 as many 130,095 inhabitants. The purpose of this study is to discharge capacity of the spring’s water still sufficient to distribute water for 10 years in the future. The evaluate the clean water distribution system in Post Administrative Dom Aleixo according to the Timor-Leste Strategic Development Plan 2011-2030, the method used is by using the Epanet 2.2 program. The data needed in Epanet 2.2 is a map of the network system, the elevation of each junction, the water discharge, pipe and the pipe roughness value. In addition to this data, there is also population data and percentage level of service, which will be used in the calculation of debits in the year of 2020-2030.